2013
DOI: 10.1097/wnr.0b013e32836140ed
|View full text |Cite
|
Sign up to set email alerts
|

Brain structure, number magnitude processing, and math proficiency in 6- to 7-year-old children born prematurely

Abstract: The aim of the present voxel-based morphometry study was to examine the link between brain structure and number skills in a group of 6-7-year-old children born prematurely, which are considered to be an at-risk population for mathematical learning disabilities. Therefore, gray and white matter density values were extracted from brain areas previously reported to be relevant for number processing in developing brain systems and, thereafter, correlated with response time results tapping semantic number knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Starke et al. () reported an association between white matter in the right IFG and the numerical distance effect in 6–7‐year‐old children, and Rotzer et al. () reported that children with Dyscalculia have decreased GM in the left IFG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Starke et al. () reported an association between white matter in the right IFG and the numerical distance effect in 6–7‐year‐old children, and Rotzer et al. () reported that children with Dyscalculia have decreased GM in the left IFG.…”
Section: Discussionmentioning
confidence: 99%
“…Cho et al (2012) demonstrated that children with higher arithmetic retrieval fluency have greater activation in the right hippocampus and parahippocampal gyrus during arithmetic problem solving, while Supekar et al (2013) showed that increased GM volume in the hippocampus was related to gains in arithmetic ability in response to a tutoring intervention. Starke et al (2013) reported an association between white matter in the right IFG and the numerical distance effect in 6-7-year-old children, and Rotzer et al (2008) domain-general functions supported by the hippocampus and IFG play a crucial role in the effective acquisition of school-relevant math skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased gray matter volume in the frontal (dorsal and ventral prefrontal cortices, IFG), occipito-temporal (cuneus, fusiform gyrus) and in the hippocampus also relates to better math performance (Li et al, 2013;Supekar et al, 2013;Evans et al, 2015;Wilkey et al, 2018). Moreover, associations between brain volume abnormalities and math performance have been reported for the gray matter volume of parietal regions in other populations prone to math difficulties (prematurely born children, very low birth weight, Turner syndrome; Isaacs et al, 2001;Starke et al, 2013;Zhao et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…The papers were identified using literature searches and cited reference searches in Web of Science. Several additional papers that originally were identified by our search ultimately were excluded because they were written in a foreign language (n = 2, Russian: Varga, Pavlova, & Nosova, 2008; German: Krick et al, 2015), focused on a special population (children born prematurely, n = 1 Starke et al, 2013), reported results that were restricted by either another task or an anatomical mask (n = 2, Berteletti, Man, & Booth, 2014; Krinzinger et al, 2011), or had stimuli that were ambiguously symbolic or nonsymbolic (fingers; n = 1, Kaufmann et al, 2008). For each of the 14 included studies, we extracted the peak coordinates from all whole-brain analyses that localized numerical processing regions.…”
Section: Uniquely Human Numerical Processingmentioning
confidence: 99%